Keeping Up Appearances: The Importance of Reputation in State – Group Relations - Kürşad TURAN (Gazi Akademik Bakış)
Over the past thirty years we observed a shift in conflict patterns where asymmetric conflicts increasingly became the norm. Building on the previous work on decision-making in asymmetric conflicts, this study compares two dominant hypotheses in the field, namely the reputation hypothesis and the capacity/interest hypothesis, regarding adversaries’ conflict behavior in asymmetric conflicts. I argue that the reputation hypothesis is more useful than its bad track record in interstate conflicts suggests. I also contend that a single hypothesis is insufficient in explaining the decision-making behavior in asymmetric conflicts. In such conflicts, the uneven nature of power/status distribution between the actors leads them to have dissimilar goals and adopt different strategies. As a result, different hypotheses may be applicable to different actors. More specifically, the state as the more powerful of the two needs to protect its reputation in order to discourage any present and future challenges. The group, on the other hand, is often the weaker actor and its choices and strategies are limited by the availability of resources. This pushes them to behave according to capacity/interest hypothesis.